Improved accuracy and reduced uncertainty in greenhouse gas inventories by refining the IPCC emission factor for direct N2O emissions from nitrogen inputs to managed soils. (25th September 2021) - Hergoualc'h, Kristell; Mueller, Nathan; Bernoux, Martial; Kasimir, Äsa; van der Weerden, Tony J.; Ogle, Stephen M.
Abstract: Most national GHG inventories estimating direct N2 O emissions from managed soils rely on a default Tier 1 emission factor (EF1 ) amounting to 1% of nitrogen inputs. Recent research has, however, demonstrated the potential for refining the EF1 considering variables that are readily available at national scales. Building on existing reviews, we produced a large dataset ( n = 848) enriched in dry and low latitude tropical climate observations as compared to former global efforts and disaggregated the EF1 according to most meaningful controlling factors. Using spatially explicit N fertilizer and manure inputs, we also investigated the implications of using the EF1 developed as part of this research and adopted by the 2019 IPCC refinement report. Our results demonstrated that climate is a major driver of emission, with an EF1 three times higher in wet climates (0.014, 95% CI 0.011–0.017) than in dry climates (0.005, 95% CI 0.000–0.011). Likewise, the form of the fertilizer markedly modulated the EF1 in wet climates, where the EF1 for synthetic and mixed forms (0.016, 95% CI 0.013–0.019) was also almost three times larger than the EF1 for organic forms (0.006; 95% CI 0.001–0.011). Other factors such as land cover and soil texture, C content, and pH were also important regulators of the EF1 . The uncertainty associated with the disaggregated EF1 was considerably reduced as compared to the range in the 2006 IPCC guidelines. Compared to estimates from the 2006 IPCC EF1, emissions based on the 2019 IPCC EF1 range from 15% to 46% lower in countries dominated by dry climates to 7%–37% higher in countries with wet climates and high synthetic N fertilizer consumption. The adoption of the 2019 IPCC EF1 will allow parties to improve the accuracy of emissions' inventories and to better target areas for implementing mitigation strategies. Abstract : The EF1 emission factor for direct N2 O emissions from nitrogen inputs to managed soils as influenced by climate, management practices (fertilizer form, N application rate), land cover, and topsoil properties (texture class, C content, alkalinity) (a). The EF1 in wet or dry climates as influenced by the same variables (b). Means and 95% confidence intervals. 2006 IPCC is the default value from the 2006 IPCC guidelines.